Tingkat Kriminalitas di Kota Banjarmasin dengan Pendekatan Ekonomi - Renny Septaria; Siti Mutmainnah Zulfaridatulyaqin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This study examines the influence of (1) the effect of income distribution inequality (Gini ratio), poverty, and job opportunity that simultaneously in crime rates (2) which one of the factors that more dominant effect in crime rates. The object of this study is Banjarmasin City. This research used secondary data in the form of time series for 12 years, started from 2007 to 2018. Data processed used multiple linear regression with software Eviews 9. This study proved that are partially variables income distribution inequality (Gini ratio) was positive and significant. At the same time, variable poverty and variable job opportunity are both positive and not significant in crime rates in Banjarmasin City. Whereas simultaneously, three independent variables were not significant in crime rates in Banjarmasin City. Then, variable income distribution inequality (Gini ratio)is the dominant effect in crime rates in Banjarmasin City.